A composite metal multi-stage pore ZSM-5 zeolite molecular sieve catalyst for synthesizing low-carbon alcohols from synthesis gas and a preparation method thereof

By embedding CuO-ZnO active components in the multi-stage pore ZSM-5 zeolite molecular sieve framework, the problems of easy sintering of traditional catalysts at high temperatures and uneven distribution of Cu-Zn are solved, and the high activity, stability and heat resistance of the catalyst are improved.

CN116139916BActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 2 Cites -1 Cited by

Patent Information

Application Number
CN202111391393.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-23
Publication Date
2025-05-02
Estimated Expiration
2041-11-23

AI Technical Summary

Technical Problem

Traditional Cu-ZnO-Al2O3 catalysts are prone to sintering and inactivation during use at high temperatures, and the distribution of Cu and Zn is uneven, resulting in insufficient anti-sintering ability and heat resistance of the catalyst.

Method used

Using a complex metal multi-stage pore ZSM-5 zeolite molecular sieve catalyst, CuO-ZnO is embedded in the framework of the multi-stage pore ZSM-5 zeolite molecular sieve, and its unique pore structure is used to improve the selectivity and stability of the catalyst.

Benefits of technology

It improves the activity and stability of the catalyst, enhances the anti-sintering ability and heat resistance, extends the service life of the catalyst, and improves the selectivity in the reaction of low-carbon alcohol in synthesis gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 167930DEST_PATH_IMAGE004
    Figure 167930DEST_PATH_IMAGE004
  • Figure 641003DEST_PATH_IMAGE002
    Figure 641003DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The present invention provides a multi-phase metal multi-stage pore ZSM-5 zeolite molecular sieve catalyst for preparing low-carbon alcohols from synthesis gas, characterized in that: the active component is a multi-phase metal oxide, and the carrier is a multi-stage pore ZSM-5 zeolite molecular sieve; wherein the molar ratio of CuO-ZnO and Cu:Zn in the multi-phase metal oxide is (1-4): 1, and the content of the active component is 20-50% by weight in terms of oxide and based on the total weight of the catalyst; SiO2:Al2O3 in the carrier is 100-200. The present invention also provides a preparation method. The present invention adopts the form of embedding the multi-phase metal into the skeleton to promote the dispersion of the active component, which is beneficial to improving the activity and stability of the catalyst; the present invention uses the multi-stage pore ZSM-5 zeolite molecular sieve as a carrier, and uses its unique pore structure to greatly improve the selectivity of the catalyst; the technical method adopted by the present invention is simple, conducive to industrial application and promotion, and has important social and economic significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a unique metal multi-stage pore ZSM-5 zeolite molecular sieve catalyst for preparing low-carbon alcohols from synthesis gas and a preparation method thereof. Background Art

[0002] As a basic chemical raw material, low-carbon alcohol is a bridge and link between coal chemical industry, natural gas chemical industry and petrochemical industry. It has great strategic significance for optimizing and adjusting the structure of my country's petrochemical industry, alleviating the contradiction between energy supply and demand, promoting the diversification and quality improvement of raw materials for chemical product production, and enhancing international market competitiveness.

[0003] At present, the most widely used catalyst for the synthesis of low-carbon alcohols in industry is Cu-ZnO-Al2O3 catalyst, in which Cu is the main catalytic active component, ZnO is the synergistic catalytic active component, and Al2O3 is used as a carrier to provide support for the active components of the catalyst. However, the Cu-ZnO-Al2O3 catalyst prepared by traditional process has a low melting point of active metal Cu, and its Tammann temperature and Hüttig temperature are very low. It is easy to sinter and deactivate when used at high temperature. To prevent the sintering of the catalyst, it is necessary to prevent and slow down the migration of active centers and Ostwald ripening, and to make the uniform and stable active center Cu fully isolated and fixed as much as possible. In the traditional preparation process, the Cu-Zn interval catalyst is obtained by coprecipitating copper nitrate and zinc nitrate, but this preparation method makes the distribution of Cu and Zn uneven. If the two are separated according to a certain structure and Zn is regularly separated from Cu, the uniform isolation of the active center of the catalyst can be achieved, and the problems of uneven distribution of active components and carriers, weak adhesion to carriers, and migration and agglomeration of active components can be solved, and the anti-sintering ability of the catalyst can be improved, its heat stability can be increased, and the service life of the catalyst can be extended. Summary of the invention

[0004] 1. Technical problems to be solved:

[0005] The most widely used catalyst for low-carbon alcohol synthesis in industry is mainly Cu-ZnO-Al2O3 catalyst. In the preparation, the active metal Cu has a low melting point, and its Tammann temperature and Hüttig temperature are very low. It is easily sintered and deactivated when used at high temperatures, and the distribution of Cu and Zn is uneven.

[0006] 2. Technical solution:

[0007] In order to solve the above problems, the purpose of the present invention is to provide a complex metal multi-stage pore ZSM-5 zeolite molecular sieve catalyst for preparing low-carbon alcohols from synthesis gas and a preparation method thereof.

[0008] The invention provides a complex metal multi-level pore ZSM-5 zeolite molecular sieve catalyst for preparing low-carbon alcohols from synthesis gas, characterized in that: the active component is a complex metal oxide, and the carrier is a multi-level pore ZSM-5 zeolite molecular sieve; wherein the molar ratio of CuO-ZnO and Cu:Zn in the complex metal oxide is (1-4):1, and the content of the active component is 20-50% by weight, calculated as oxide and based on the total weight of the catalyst; and the SiO2:Al2O3 in the carrier is 100-200.

[0009] The BET specific surface area of ​​the catalyst is 400-500 m2 / g; the average pore diameter is 8-20 nm; and the pore volume is 0.5-0.8 cm3 / g.

[0010] The catalyst can be used for the reaction of preparing low-carbon alcohols from synthesis gas.

[0011] The present invention also provides a preparation method of the multi-phase metal multi-level pore ZSM-5 zeolite molecular sieve catalyst for preparing low-carbon alcohols from synthesis gas, comprising the following steps: 1) dissolving aluminum isopropoxide, an organic ammonium template agent, and an alkali metal compound in ethanol to obtain a solution after all of them are dissolved, adding silica sol or tetraethyl orthosilicate to the solution under stirring, and continuously stirring for 0.5-2h to obtain a carrier mixture gel, controlling the reaction temperature at 50-70°C, and air-drying the gel under negative pressure to form a dry gel after the stirring is completed; 2) mixing a nitrate solution of an active component, and slowly adding the mixture to the dry gel obtained in step 1); 3) loading the catalyst precursor obtained in step 2) into a reaction kettle with a polytetrafluoroethylene liner, placing the reaction kettle in an oven, and subjecting the reaction kettle to temperature control treatment; 4) pouring out the product in step 3), washing, filtering, drying, granulating, and calcining, and finally adding water and a binder to extrusion molding.

[0012] In step 1), the organic template is one of tetrabutylammonium bromide and tetrapropylammonium bromide.

[0013] In step 1), the alkali metal oxide is one of NaOH, KOH, Na2CO3, and K2CO3.

[0014] In step 3), the temperature control treatment is carried out at a temperature of 200-300° C. for 48 h to 96 h.

[0015] In step 4), the calcination temperature is 400° C.-500° C., and the calcination time is 3-4 hours.

[0016] 3. Beneficial effects:

[0017] The present invention adopts the form of embedding a complex metal into a skeleton to promote the dispersion of active components, which is beneficial to improving the activity and stability of the catalyst; the present invention uses a multi-level pore ZSM-5 zeolite molecular sieve as a carrier and utilizes its unique pore structure to greatly improve the selectivity of the catalyst; the technical method adopted by the present invention is simple, which is conducive to industrial application and promotion and has important social and economic significance. DETAILED DESCRIPTION

[0018] The following examples are only used to further explain the content and effects of the present invention, rather than to limit the present invention.

[0019] Example 1

[0020] According to the active component accounting for 40% of the total mass, Cu:Zn=1:1, SiO2:Al2O3 is 100, weigh 11.6g zinc nitrate, 18.4g copper nitrate hexahydrate, 29.5g 40% silica sol, 0.8g aluminum isopropoxide, 5.06g tetrabutylammonium bromide, 5gNaOH, dissolve aluminum isopropoxide, tetrabutylammonium bromide, and NaOH in 30ml anhydrous ethanol solution, and after all dissolved, add silica sol solution at 50℃ under stirring, continue stirring for 0.5h, pour out the gel after the end, and air-dry under negative pressure to form a dry gel; prepare 25ml aqueous solution of copper nitrate and zinc nitrate, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 250℃ for 72h; pour out the product, wash, filter, dry, granulate, and roast at 450℃ for 4h, finally add water and binder to extrude and form, and obtain catalyst C1.

[0021] Example 2

[0022] According to the active component accounting for 20% of the total mass, Cu:Zn=2:1, SiO2:Al2O3 is 100, weigh 3.9g zinc nitrate, 12.3g copper nitrate hexahydrate, 39.3g 40% silica sol, 1.07g aluminum isopropoxide, 6.8g tetrabutylammonium bromide, 5.8g NaOH, dissolve aluminum isopropoxide, tetrabutylammonium bromide, and NaOH in 30ml anhydrous ethanol solution, and after all dissolved, add silica sol solution at 70°C under stirring, continue stirring for 2h, pour out the gel after the end, and air-dry under negative pressure to form a dry gel; prepare 25ml aqueous solution of copper nitrate and zinc nitrate, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 300°C for 48h; pour out the product, wash, filter, dry, granulate, and roast at 500°C for 3h, finally add water and a binder to extrude and form, and obtain catalyst C2.

[0023] Example 3

[0024] According to the active component accounting for 50% of the total mass, Cu:Zn=4:1, SiO2:Al2O3 is 200, weigh 5.8g zinc nitrate, 36.9g copper nitrate hexahydrate, 24.8g 40% silica sol, 0.34g aluminum isopropoxide, 2.1g tetrabutylammonium bromide, 4.6gKOH, dissolve aluminum isopropoxide, tetrabutylammonium bromide, and KOH in 30ml anhydrous ethanol solution, and after all are dissolved, add silica sol solution at 60°C under stirring, continue stirring for 1h, pour out the gel after the end, and air-dry under negative pressure to form a dry gel; prepare 25ml aqueous solution of copper nitrate and zinc nitrate, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 200°C for 96h; pour out the product, wash, filter, dry, granulate, and roast at 400°C for 6h, and finally add water and a binder to extrude and form a strip to obtain catalyst C3.

[0025] Example 4

[0026] Based on the active component accounting for 30% of the total mass, Cu:Zn=3:1, SiO2:Al2O3 is 150, weigh 4.4g zinc nitrate, 20.7g copper nitrate hexahydrate, 34.6g 40% silica sol, 0.63g aluminum isopropoxide, 4.0g tetrabutylammonium bromide, 6.7g Na2CO3, dissolve aluminum isopropoxide, tetrabutylammonium bromide and Na2CO3 in 30ml of anhydrous ethanol solution. After all of them are dissolved, add silica sol solution into it at 55°C under stirring, and continue stirring for 1.5h. After the end, pour out the gel and air-dry it into a dry gel under negative pressure; prepare 25ml of copper nitrate and zinc nitrate into a 25ml aqueous solution, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 350°C for 48h; pour out the product, wash, filter, dry, granulate, and roast at 350°C for 4h, finally add water and a binder to extrude it into strips to obtain catalyst C4.

[0027] Example 5

[0028] According to the active component accounting for 20% of the total mass, Cu:Zn=2:1, SiO2:Al2O3 is 180, weigh 3.9g zinc nitrate, 12.3g copper nitrate hexahydrate, 82.4g tetraethyl orthosilicate, 0.6g aluminum isopropoxide, 3.1g tetrapropylammonium bromide, 7.1g K2CO3, dissolve aluminum isopropoxide, tetrapropylammonium bromide, and K2CO3 in 30ml anhydrous ethanol solution, and after all dissolved, add tetraethyl orthosilicate under stirring at 60°C, continue stirring for 2h, pour out the gel after the end, and air-dry under negative pressure to form a dry gel; prepare 25ml aqueous solution of copper nitrate and zinc nitrate, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 350°C for 72h; pour out the product, wash, filter, dry, granulate, and roast at 360°C for 5h, finally add water and a binder to extrude and form a strip, and obtain catalyst C5.

[0029] Example 6

[0030] According to the active component accounting for 30% of the total mass, Cu:Zn=2:1, SiO2:Al2O3 is 120, weigh 5.8g zinc nitrate, 18.4g copper nitrate hexahydrate, 71.8g tetraethyl orthosilicate, 0.8g aluminum isopropoxide, 4.1g tetrapropylammonium bromide, 7.4g K2CO3, dissolve aluminum isopropoxide, tetrapropylammonium bromide, and K2CO3 in 30ml anhydrous ethanol solution, and after all dissolved, add tetraethyl orthosilicate under stirring at 60°C, continue stirring for 2h, pour out the gel after the end, and air-dry under negative pressure to form a dry gel; prepare 25ml aqueous solution of copper nitrate and zinc nitrate, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 350°C for 72h; pour out the product, wash, filter, dry, granulate, and roast at 380°C for 4h, finally add water and a binder to extrude and form a strip, and obtain catalyst C6.

[0031] Example 7

[0032] Based on the active component accounting for 40% of the total mass, Cu:Zn=3:1, SiO2:Al2O3 is 100, weigh 5.8g zinc nitrate, 27.7g copper nitrate hexahydrate, 61.4g tetraethyl orthosilicate, 0.8g aluminum isopropoxide, 4.2g tetrapropylammonium bromide, 5.3g KOH, dissolve aluminum isopropoxide, tetrapropylammonium bromide, and KOH in 30ml anhydrous ethanol solution, and after all dissolved, add tetraethyl orthosilicate under stirring at 70°C, continue stirring for 2h, pour out the gel after the end, and air-dry under negative pressure to form a dry gel; prepare 25ml aqueous solution of copper nitrate and zinc nitrate, put it into a reactor with a polytetrafluoroethylene liner together with the dry gel, and treat it at 350°C for 72h; pour out the product, wash, filter, dry, granulate, and roast at 380°C for 4h, finally add water and a binder to extrude and form a strip, and obtain catalyst C6.

[0033] Example 8

[0034] The catalyst was applied to the synthesis gas to methanol reaction, using a micro-fixed bed continuous flow reactor, with a catalyst loading of 2mL and a particle size of 16-40 mesh. The catalyst was reduced in a low hydrogen (H2:N2=5:95) atmosphere, with a programmed temperature increase (20℃ / h) for 10 hours, and the temperature was raised to 230℃. The reducing gas was switched to the raw gas for activity testing. The activity test conditions were a reaction pressure of 8.0MP and a space velocity of 10000h -1, temperature 230℃, synthesis gas composition: H2:CO:CO2:N2 = 65:14:4:17 (v / v), after the reaction is stable for 2h, the liquid in the liquid collector is emptied and the timing is started. The collector is cooled by circulating water. After 2.5h, the collector liquid (crude methanol) is collected, weighed, and chromatographically analyzed. The measurement result is the initial activity. After the catalyst is heat treated for 5 hours under synthesis gas atmosphere, normal pressure, and 400 °C, it is restored to the above activity evaluation conditions. The measured activity result is the heat-resistant activity. The comparison sample is a methanol catalyst purchased on the market.

[0035] Table 1 Activity evaluation results

[0036]

[0037] It can be seen from Table 1 that when the catalyst of the present invention is used in the synthesis gas to methanol reaction, the initial activity and the activity after heat resistance are significantly higher than those of the catalyst sample prepared by the traditional process, and can meet the industrial production conditions.

[0038] Example 9

[0039] The catalyst was applied to the reaction of synthesizing isobutanol from synthesis gas. The original catalyst particle size was loaded into a reactor with an inner diameter of 26 mm, with a loading volume of 50 ml, and the catalyst performance was evaluated. Before the reaction, the catalyst was reduced for 12 hours at 400°C, 0.2MPa, and a 5% hydrogen concentration nitrogen and hydrogen atmosphere, and then the pressure was increased and switched to synthesis gas for reaction. The reaction conditions were: pressure 8.0MPa, temperature 380°C, synthesis gas GHSV = 3800h -1 , H2 / CO=3:1.

[0040] Table 2 Activity evaluation results

[0041]

[0042] It can be seen from Table 2 that the catalyst of the present invention has good activity and isobutanol selectivity when used in the reaction of preparing isobutanol from synthesis gas, which shows that the catalyst of the present invention can be well applied to the reaction of preparing low-carbon alcohols from synthesis gas.

Claims

1. A method for preparing a multiphase metal multi-stage pore ZSM-5 zeolite molecular sieve catalyst for synthesizing low-carbon alcohols from synthesis gas, characterized in that: The active component is a complex metal oxide, and the carrier is a multi-level pore ZSM-5 zeolite molecular sieve; wherein the molar ratio of Cu:Zn in the complex metal oxide CuO-ZnO is (1-4):1, and the content of the active component is 20-50% by weight, calculated as oxide and based on the total weight of the catalyst; the ratio of SiO2:Al2O3 in the carrier is 100-200; the preparation method of the catalyst comprises the following steps: 1) first dissolving aluminum isopropoxide, an organic ammonium template, and an alkali metal compound in ethanol, and obtaining a solution after all of them are dissolved, and adding silica sol or tetraethyl orthosilicate to the above solution under stirring; ester, stirring continuously for 0.5-2h to obtain a carrier mixture gel, controlling the reaction temperature at 50-70°C, and after stirring, air-drying the gel under negative pressure to form a dry gel; 2) mixing the nitrate aqueous solution of the active component, and slowly adding it to the dry gel obtained in step 1); 3) loading the catalyst precursor obtained in step 2) into a reaction kettle with a polytetrafluoroethylene liner, placing the reaction kettle in an oven, and controlling the temperature, the treatment temperature is 200-300°C, and the treatment time is 48-96h; 4) pouring out the product in step 3), washing, filtering, drying, granulating, roasting, and finally adding water and a binder to extrude into strips.

2. The preparation method according to claim 1, characterized in that: BET specific surface area is 400-500m 2 / g; average pore diameter is 8-20nm; pore volume is 0.5-0.8cm 3 / g.

3. The preparation method according to claim 1, characterized in that: In step 1), the organic template is one of tetrabutylammonium bromide and tetrapropylammonium bromide.

4. The preparation method according to claim 1, characterized in that: In step 1), the alkali metal compound is one of NaOH, KOH, Na2CO3, and K2CO3.

5. The preparation method according to claim 1, characterized in that: In step 4), the calcination temperature is 400-500° C. and the calcination time is 3-4 hours.

Citation Information

Patent Citations

  • Preparation method and application of hierarchical porous ZSM-5 molecular sieve

    CN108658093A

  • Synthesis method of hierarchical porous ZSM-5 molecular sieve anchored palladium nanoparticles

    CN110038627A